Evaluating posterior vitreous detachment by widefield 23-mm swept-source optical coherence tomography imaging in healthy subjects - Chiku, Yoshiaki; Hirano, Takao; Takahashi, Yoshiaki; Tuchiya, Ayako; Nakamura, Marie; Murata, Toshinori (Scientific reports, 2021)
Posterior vitreous detachment (PVD) is a separation between the posterior vitreous cortex and internal limiting membrane. Although PVD was historically considered an acute event, recent studies using spectral-domain optical coherence tomography (SD-OCT) revealed a gradual progression of PVD in healthy subjects. Although SD-OCT improved PVD studies, the narrow imaging angle and long examination time were problematic to allow wide angle capture. The Xephilio OCT-S1 (Canon), a swept-source OCT (SS-OCT) device, can obtain up to 23-mm of widefield B-scan images in a single acquisition. We used this widefield SS-OCT to quantitatively evaluate the PVD stage in 214 healthy subjects aged 4–89 years and determine whether PVD stages differ between the bilateral eyes of each patient. Age was significantly positively correlated with the overall PVD stage (ρ = 0.7520, P < 0.001). Interestingly, partial PVD occurred in children as young as 5 years, indicating that initial PVD onset may occur much earlier than previously reported. Furthermore, PVD stages of the bilateral eyes were highly consistent in 183 subjects (85.5%). Widefield 23-mm SS-OCT thus revealed that PVD started earlier than anticipated, and age was correlated with the symmetry of PVD stage. Widefield 23-mm SS-OCT may also be clinically useful for the evaluation of diseased eyes.